THE EFFECTIVENESS OF FOOT REFLECTION MASSAGE THERAPY CONTROLLING BLOOD PRESSURE PATIENTS HYPERTENSION IN THE FAMIL: SYSTEMATIC REVIEW - Siregar, Yaumil Hafsani (Poltekkes Kemenkes Medan, 2024)
Hypertension is a chronic condition characterized by increased blood pressure on the walls of the arteries. Interventions for hypertension sufferers can be controlled by providing pharmacological and non-pharmacological therapy, one of which is foot reflexology massage. This therapy is massaging the reflex points on the feet which is done by rubbing slowly and regularly to increase relaxation and control blood pressure. This Systematic Review aims to identify effectiveness of massage therapy foot sole reflexology in controlling blood pressure in hypertensive patients in the family. Search for articles using databases including: PubMed and Google Scholar with inclusion criteria, namely: full text, in the period 2019-2024, has a DOI, Randomized Control Trials (RCT) research type. From the literature search, 6 articles were obtained that met the criteria for conducting the study. The six articles state that providing foot reflexology massage can control blood pressure, reduce stress and improve the quality of life of hypertension patients in the family. Foot reflexology massage is effective for controlling blood pressure and improving the quality of life for patients and their families.